Between Tradition and Modernity: Reclaiming Women’s Agency through the Exegeses of Zainab al-Ghazali and Wahbah Az-Zuhaili - Abdullah Safei; Muhammad Irawan Taqwa (ZAD Al-Mufassirin, 2026)
This article aims to examine the status of women in Islam by analyzing verses of the Qur’an through a thematic (Maudhu’i) exegetical approach, as well as to compare the interpretations of the female exegete Zainab al-Ghazali in Nazarāt fī kitābillah and the contemporary exegete Wahbah az -Zuhaili in Tafsīr al-Munīr. This study offers a new contribution through a comparative approach between female and male exegetes regarding verses pertaining to women in the Qur’an. The method used is descriptive qualitative with a library research approach. Primary data comes from the two exegetical works that are the focus of the study, while secondary data consists of books, scholarly articles, and other supporting sources. The analysis was conducted by comparing their interpretations of 10 relevant verses regarding the status of women. The results of this study indicate that both Zainab al-Ghazali and Wahbah az-Zuhaili share aligned perspectives regarding the recognition of women’s roles in both domestic and public spheres. However, Zainab al-Ghazali places greater emphasis on the aspect of women’s internal struggle, whereas Wahbah az-Zuhaili adopts a more normative and textual approach. This study also concludes that the contributions of both thinkers remain relevant for addressing various women’s issues in the modern era, particularly regarding equality, social roles, inheritance rights, leadership, and the social stigma attached to women.